The good struggle : responsible leadership in an unforgiving world - Badaracco, Joseph (Boston, Massachusetts : Harvard Business Review Press, 2013)
The question of how to lead successfully and responsibly is crucially important in our uncertain, high-pressure, turbulent world. In this book, Harvard Business School Professor Joseph Badaracco answers this question in practical and, at times, provocative ways. Leaders today are surrounded by what Badaracco calls "the new invisible hand"--powerful, pervasive markets that touch and shape almost everything. As a result, understanding the inevitability and importance of struggle is critical. And leaders must go a step further to create what Badaracco calls "the good struggle" in order to meet their goals at work, as well as their goals in life. The Good Struggle helps you meet the relentless challenges of being a leader today by identifying the most important questions you should be asking yourself. New answers to these questions can be found by watching leaders in dynamic settings, especially entrepreneurs. The conditions entrepreneurs have always faced--intense competition, scarce resources, and unforgiving markets--are true now for the rest of us, and they offer valuable, practical lessons about struggling and succeeding in volatile and uncertain environments. If "the joy of life is in the struggle," as one thoughtful entrepreneur put it, The Good Struggle can help you find meaning in your work, stay focused on what matters despite the turbulence around you, and keep you on the path to leading successfully and responsibly.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Leadership; Social responsibility of business; Corporate Social Responsibility; Führung; Unternehmensethik; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books